Pengaruh E-Service Quality, Persepsi Harga dan Promosi Penjualan Terhadap Loyalitas Pelanggan Grab di Universitas KH. A. Wahab Hasbullah - Ita Rahmawati; Lailatus Sa’adah; Rahmania Hidayatus Sholikah (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This study aims to determine the effect of e-service quality, price perceptions, and sales promotions on customer loyalty (a study on Grab online transportation service customers at KH. A. Wahab Hasbullah University, Jombang). This research uses quantitative methods with type research used, namely surveys. The population in this study are students of the economics faculty who use the Grab online transportation service. The sampling technique used purposive sampling, with a total sample of 80 respondents. The data collection technique uses an online questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression, coefficient of determination R2, T-test, and F-test. The results of this study show 1) There is no effect of e-service quality on customer loyalty study on Grab online transportation service customers at KH University. A. Wahab Hasbullah Jombang. 2) There is an influence of price perceptions on customer loyalty study on Grab online transportation service customers at KH University. A. Wahab Hasbullah Jombang. 3) There is an effect of sales promotion on customer loyalty study on Grab online transportation service customers at KH University. A. Wahab Hasbullah Jombang. 4) There is the effect of e-service quality, price perception, and sales promotion simultaneously on customer loyalty study on Grab online transportation service customers at KH University. A. Wahab Hasbullah Jombang.